The Effect of Teams Games Tournamenty (TGT) Models Containing Science Literacy on Student’s Learning Competencies in Respiratory System Human Material - Tika Apriani Risdiyanto; Syamsurizal Syamsurizal; Relsas Yogica; Elsa Yuniarti (ATRIUM PENDIDIKAN BIOLOGI, 2019)
This research is based on the problems that exist at junior high school 28 padang, namely the learning model that is less varied, students' learning competencies are still low. Efforts that can be done are applying thelearning model teams games tournament (TGT) with scientific literacy in the  Respiratory  system material at 28 Padang Junior High School. The purpose of this study was to determine the effect of the application of thelearning model that Teams Games Tournamen (TGT) contained scientific literacy to the learning competencies of Grade VIII students of 28 SMP Negeri Padang. This research is an experimental research with randomized control group posttest only design. The study population is the students of class VIII Junior high school 28 padang 2018/2019 academic year which spread into nine classes. Sampling research using simple random sampling. The results were selected class VIII.3 as experimental class and class VIII.5 as a control class. The hypothesis in this study was tested using the t-test. The results of the study using the t-test it can be concluded that the competency of students' knowledge of the value of tcount 3,34> ttable 1.67, in the competency attitude the value of tcount is 1,84> ttable 1.67, and the competence of value skills tcount 1,85> ttable 1.67. This shows that the hypothesis is accepted. So, it can be concluded that the application of TGT models with scientific literacy can improve the competency of knowledge, attitudes, and skills of class VIII students of junior high school 28 Padang.